Characterisation of Listeria monocytogenes isolates from cattle using a bovine caruncular epithelial cell model. Issue 7 (July 2020) - Blanchard, Adam M.; Billenness, Rosemarie; Warren, Jessica; Glanvill, Amy; Roden, William; Drinkall, Emma; Maboni, Grazieli; Robinson, Robert S.; Rees, Catherine E.D.; Pfarrer, Christiane; Tötemeyer, Sabine
Abstract: Listeria monocytogenes is an important foodborne pathogen in human and veterinary health, causing significant morbidity and mortality including abortion. It has a particular tropism for the gravid uterus, however, the route of infection in reproductive tissues of ruminants (i.e. placentome), is much less clear. In this study, we aimed to investigate a bovine caruncular epithelial cell (BCEC) line as a model for L. monocytogenes infection of the bovine reproductive tract. The BCEC infection model was used to assess the ability of 14 different L. monocytogenes isolates to infect these cells. Lysozyme sensitivity and bacterial survival in 580 μg lysozyme/ml correlated with attenuated ability to proliferate in BCEC (p = 0.004 and p = 0.02, respectively). Four isolates were significantly attenuated compared to the control strain 10403S. One of these strains (AR008) showed evidence of compromised cell wall leading to increased sensitivity to ß-lactam antibiotics, and another (7644) had compromised cell membrane integrity leading to increased sensitivity to cationic peptides. Whole genome sequencing followed by Multi Locus Sequence Type analysis identified that five invasive isolates had the same sequence type, ST59, despite originating from three different clinical conditions. Virulence gene analysis showed that the attenuated isolate LM4 was lacking two virulence genes ( uhpT, virR ) known to be involved in intracellular growth and virulence. In conclusion, the BCEC model was able to differentiate between the infective potential of different isolates. Moreover, resistance to lysozyme correlated with the ability to invade and replicate within BCEC, suggesting co-selection for surviving challenging environments as the abomasum. Abstract : Bioinformatics; Genetics; Microbiology; Molecular biology; Listeria monocytogenes ; infection model; BCEC; MLST, sequence typing.